Labour relations in comparative perspective: Special focus on the SME sector (part 2) - Csaba Makó; Péter Csizmadia; Miklós Illéssy (Journal for East European Management Studies, 2006)
The evolution of the view and practice of social partnership is one basic element in the construction of the European Union. The paper gives an overview on the key actors and institutions of Labour Relations System (LRS) with special focus on the micro- small and medium sized enteprises (SME). In the first section, the author describes the key social partners and institutions of the LRS in the countries participating in an international research project carried out in 2003-2006. The second section of the paper deals with the particular features of the LRS in the SME sector. The strong informality of social dialogue is the key institutional pattern of LRS in the SME sector. – – Die Evolution der Betrachtung und Anwendung von 'sozialen Partnerschaften' ist ein Basiselement für die Entwicklung der Europäischen Union. Dieser Aufsatz gibt einen Überblick über die Hauptakteure und Institutionen des Systems der industriellen Beziehungen (IB), mit einem speziellen Augenmerk auf kleine und mittelständische Unternehmen (KMU). Im ersten Abschnitt beschreibt der Autor die wichtigsten sozialen Partner und Institutionen der IB in den Ländern, die 2003-2006 an einem internationalen Forschungsprojekt teilnahmen. Der zweite Teil behandelt die spezifischen Eigenschaften des IB im KMU-Sektor. Die ausgeprägte Informalität des sozialen Dialogs ist ein wichtiges institutionelles Muster der IB im KMU-Sektor.
Keywords: 650; LabourRelations System; Social Actors and Institutions; Collective Bargaining; Works Council; Informal Regulation; SME